Age- and Sex-Associated Glucose Metabolism Decline in a Mouse Model of Alzheimer's Disease - Gherardelli, Camila; Cisternas, Pedro; Vera-Salazar, Roberto F.; Mendez-Orellana, Carolina; Inestrosa, Nibaldo C. (My University, 2022)
Background: Alzheimer's disease (AD) is characterized by a high etiological and clinical heterogeneity, which has obscured the diagnostic and treatment efficacy, as well as limited the development of potential drugs. Sex differences are among the risk factors that contribute to the variability of disease manifestation. Unlike men, women are at greater risk of developing AD and suffer from higher cognitive deterioration, together with important changes in pathological features. Alterations in glucose metabolism are emerging as a key player in the pathogenesis of AD, which appear even decades before the presence of clinical symptoms. Objective: We aimed to study whether AD-related sex differences influence glucose metabolism. Methods: We used male and female APPswe/PS1dE9 (APP/PS1) transgenic mice of different ages to examine glucose metabolism effects on AD development. Results: Our analysis suggests an age-dependent decline of metabolic responses, cognitive functions, and brain energy homeostasis, together with an increase of A beta levels in both males and females APP/PS1 mice. The administration of Andrographolide (Andro), an anti-inflammatory and anti-diabetic compound, was able to restore several metabolic disturbances, including the glycolytic and the pentose phosphate pathway fluxes, ATP levels, AMPK alpha activity, and Glut3 expression in 8-month-old mice, independent of the sex, while rescuing these abnormalities only in older females. Similarly, Andro also prevented A beta accumulation and cognitive decline in all but old males. Conclusion: Our study provides insight into the heterogeneity of the disease and supports the use of Andro as a potential drug to promote personalized medicine in AD.
Keywords: alzheimer's disease; andrographolide; glucose metabolism; neuroprotection; sex differences